Keeping Up with the Quants - Davenport, Tom; Kim, Jinho (HighBridge, 2014)
Welcome to the age of data. No matter your interests (sports, movies, politics), your industry (finance, marketing, technology, manufacturing), or the type of organization you work for (big company, nonprofit, small start-up), your world is awash with data. As a successful manager today, you must make sense of all this information. You need to be conversant with analytical terminology and methods and able to work with quantitative information. This book promises to be your "quantitative literacy" guide-helping you develop the analytical skills needed right now in order to summarize data, find the meaning in it, and extract its value.